Improved Quantification of Global Mean Ocean Mass Change Using GRACE Satellite Gravimetry Measurements. Issue 23 (3rd December 2019) - Chen, Jianli; Tapley, Byron; Seo, Ki‐Weon; Wilson, Clark; Ries, John
Key Points: GRACE‐derived global ocean mass change agrees remarkably well with Altimeter‐Argo estimates at both seasonal and long‐term scales Appropriate implementation of global mass conservation is important in GRACE global mean ocean mass change estimation Retaining GRACE ΔJ2 coefficients provides better GRACE ocean mass estimates at both seasonal and long‐term scales Abstract: Global mean ocean mass change derived from the Gravity Recovery and Climate Experiment (GRACE) gravity solutions generally agrees well with ocean mass change inferred from satellite altimeter sea surface height and Argo floats observations during the period January 2005 to December 2015. However, there is a systematic annual phase lag (~10°) between GRACE and Altimeter‐Argo estimates. This phase lag is attributed to the enforced mass conservation in GRACE gravity solutions, in which the ΔC00 coefficients (representing changes in total Earth mass) are set to zero. After a correct implementation of global mass conservation by removing global mean atmospheric mass from the GRACE solutions using atmospheric model predictions, the annual phase lag is nearly completely gone, yielding significantly improved agreement between GRACE and Altimeter‐Argo estimates. In addition, retaining GRACE ΔJ2 coefficients provides better GRACE ocean mass estimates at both seasonal and long‐term time scales.